A UAV-Based Dye-Tracking Technique to Measure Surface Velocities over Tidal Channels and Salt Marshes - Daniele Pinton; Alberto Canestrelli; Luca Fantuzzi (Journal of Marine Science and Engineering, 2020)
An accurate description of hydrodynamic processes in coastal wetlands is needed to improve their management and conservation. As a consequence, higher knowledge of the connected morphological and ecologic processes is achievable. However, it is very costly to collect spatially distributed values of flow velocities over tidal channels and intertidal areas by means of in situ sensors. Also, when deploying sensors, humans perturb the ecosystem, which takes time to recover. In this study, a new low-cost unmanned aerial vehicle (UAV)-based method to measure surface velocities is proposed and validated. The study area is a salt marsh system on the southeast coast of Little Sapelo Island, Georgia, USA. Two unmanned aerial vehicles were used in the survey. A first UAV released a fluorescent dye tracer on marshes and tidal creeks, while a second one tracked its movement by collecting RGB images. Flow direction and magnitude were calculated from the images using a newly developed algorithm. A comparison with velocities measured with an acoustic Doppler current profiler confirmed the effectiveness of the method. Our results indicate that the calculated flow field is affected by vegetation, marsh morphology, and marsh width. In particular, a non-negligible velocity component perpendicular to the creek axes is detected both in ebb and in flood. Our technique proves to be an effective, non-intrusive, low-cost way to survey the two-dimensional hydrodynamics on salt marsh environments at a km scale. Collected data would be beneficial for calibrating and validating numerical models with accurate water flux information.